Gestión administrativa del Cyber y multiservicios ML en la ciudad de Babahoyo del periodo 2022. - Guerrero Modragon, Dixon Noe (2023)
Through the present case study called "Administrative Management of Cyber and Multiservices ML in the City of Babahoyo for the Period 2022" related to the line of research "Financial, Administrative, Tax, Audit and Control Management" and the sub-line of the "Marketing and Commercialization" career, aims to analyze the processes related to the administration in order to choose a course of action that helps to achieve the established objectives and that allows to listen for contingencies in the future that disturb the organization. Through the investigation it was possible to identify weaknesses in the direction of the business, deficient administrative management and little supervision of the activities carried out by the staff. To obtain information, the deductive and analytical method was implemented, through which it was possible to obtain data related to both administrative management, as well as the analysis of the different problematic causes; the processes related to the business action of the business, allowing to identify the factors that affect the normal development of the activities, considering the use of techniques such as the survey directed to the employees of the company and the interview applied to the business owner that allowed obtaining Relevant information on the development of activities, determine which are the important factors for an adequate action to manage, with the purpose of optimizing the human, technological and economic resources that the company has.